Digital Forensik dalam Upaya Mengedukasi Masyarakat Berperilaku Sehat di Media Sosial - Sritumini, Bella Annantha; Nuraini, Aisyah (Jurnal Pengabdian Tri Bhakti, 2021)
Social Media has an important role during the Covid-19 pandemic, namely by facilitating new forms of social interaction, dialogue, information exchange and collaboration. It enables all users and organizations in the world to exchange ideas, post comments, and participate in activities and events and share their wider interests. At the same time, such a phenomenon has led to a significant increase in criminal activity by perpetrators who are increasingly sophisticated in their attempts to use technology to evade detection. In Indonesia, the trend of cyber crime is increasing with various types of crime. Many people take irresponsible actions through social media and can avoid punishment because these actions are carried out in cyberspace, while people are affected by direct material and moral losses. This is certainly unfair, so it is necessary to educate the public on healthy behavior using social media and acting wisely. If a crime is committed, an investigation of digital evidence can be carried out so that it can be sued in accordance with the applicable ITE law By promoting healthy behavior on social media and explaining the steps of digital investigations to the public, it is hoped that it can suppress crime in cyberspace and obtain optimal benefits from social media. The planned activities include (1) preparation of the required resources in the PKM. (2) Implementing a program with a training model between the PKM team from UNLA and the community (3). In the training on healthy behavior on social media, the last one is (4) evaluation and reporting of activities.